Challenges in clinical diagnosis of Clade I Mpox: Highlighting the need for enhanced diagnostic approaches. - Josephine Bourner; Esteban Garcia-Gallo; Festus Mbrenga; Yap Boum; Emmanuel Nakouné; Amy Paterson; Benjamin Jones; Piero Olliaro; Amanda Rojek (Public Library of Science (PLoS), 2024)
Background Due to limited diagnostic capacity and availability of point-of-care tests, diagnosis of Clade I mpox in the geographical regions most affected is usually on clinical grounds. This may be complicated due to the similarity between mpox and varicella (chickenpox) lesions. Visual assessment of lesions is also used for determining clinical progress and to assess patient outcomes in clinical trials. However, there has been no investigation into whether clinicians can (i) identify Clade I mpox compared to other viral lesions (ii) differentiate between Clade I mpox lesion stages. Methodology/principle findings The objective of this study was to evaluate inter-rater reliability and agreement between clinicians assessing lesions in patients with Clade I mpox. We presented experienced clinicians with 17 images of Clade I mpox or varicella and asked them to independently indicate the most likely diagnosis-mpox or varicella-and to categorise the lesions according to their stage. When selecting the most likely diagnosis, accuracy varied across all images, the inter-rater reliability was poor (κ = 0.223; z = 10.1) and agreement was moderate (Po = 68%). When categorising lesions according to their type, if a single lesion type was present in the image, inter-rater reliability was moderate (κ = 0.671, z = 40.6) and agreement was good (Po = 78%), but when multiple lesion types were shown in an image, both inter-rater reliability (κ = 0.153, z = 10.5) and agreement (Po = 29%) decreased substantially. Conclusions This study demonstrates that there are presently limitations in using visual assessment to diagnose Clade I mpox and evaluate lesion stage and treatment outcomes, which have an impact on clinical practice, public health and clinical trials. More robust indicators and tools are required to inform clinical, public-health, and research priorities, but these must be implementable in countries affected by mpox.